Identification of Relevant Scientific Articles using a Modified Naive Bayes Classifier - Dvornikov, Dmitrii; Ilin, Dmitry; Kotilevets, Igor; Ivanova, Irina; Stepanova, Anna (2022 2nd International Conference on Technology Enhanced Learning in Higher Education (TELE), 2022)
The rapid growth in the number of scientific publications increases researchers' need for systems that provide quick access to the most relevant articles on their subjects of interest. Existing solutions do not have enough flexibility to adapt to the needs of each user of the system. This study presents a scientific articles recommendation mechanism which takes into account the user's individual preferences. The precision of the recommendations is 70%.